Interpreting hydrogeochemical interactions and controlling processes in groundwater using advanced statistical techniques in the Southeast Asian megacity: Dhaka, Bangladesh - Mahir Tajwar; Mahfuzur Rahman; Mahmudul Hasan; Nazmus Sakib; Shamiha Shafinaz Shreya; Mir Md Tasnim Alam; Md. Yousuf Gazi; Sharaf Anika Hoque; Anwar Zahid (Cleaner Water)
Groundwater quality is under increasing threat in rapidly urbanizing Southeast Asian megacities, where unregulated expansion and industrial activity are altering subsurface geochemical conditions. In Dhaka, Bangladesh, groundwater serves as a crucial source of potable water for millions, necessitating rigorous assessment of its suitability for human and agricultural use. This research seeks to comprehensively assess the hydrogeochemical characteristics of shallow groundwater, evaluating its suitability for both drinking and irrigation purposes using a combined approach of geochemical methods, multivariate statistical analyses, and geospatial techniques. The hydrogeochemical analysis of 15 groundwater samples revealed a cation order of Ca2 + > Na+ > Mg2+ > K+ and an anion order of HCO3− > Cl− > SO42− > NO3−. The primary objective of this research is to assess the hydrogeochemical characteristics and water quality of shallow groundwater in Dhaka using a combination of graphical techniques, multivariate statistical analyses, and water quality indices. Fifteen groundwater samples were collected during the dry season and analyzed for major cations and anions. Piper, Gibbs, Durov, and Stiff diagrams were employed to identify dominant processes. Principal Component Analysis (PCA) and hierarchical clustering were used to distinguish geogenic and anthropogenic influences. Results revealed that groundwater is dominated by the calcium bicarbonate type, with cation order Ca²⁺ > Na⁺ > Mg²⁺ > K⁺ and anion order HCO₃⁻ > Cl⁻ > SO₄²⁻ > NO₃⁻. Cation exchange and silicate weathering were identified as the significant processes influencing water chemistry. PCA revealed that three principal components accounted for 86.4 % of the variance, indicating the influence of both natural mineral dissolution and localized anthropogenic inputs. According to the Water Quality Index (WQI), 5 samples were excellent, 6 were good, and 4 were poor for drinking purposes. All samples were suitable for irrigation based on SAR, RSC, SSP, EC, and TDS values. These findings provide a robust baseline for groundwater quality monitoring in Dhaka and similar urban areas. The integrated methodology can guide policy decisions on water resource protection and help communities prioritize safe groundwater use for both domestic and agricultural needs. The study offers valuable information for assessing water quality, monitoring contamination risks, and developing groundwater management strategies, particularly in rapidly urbanizing regions of Southeast Asia.